The Dividing Line Between Wildlife Research and Management—Implications for Animal Welfare - Lindsjö, Johan; Cvek, Katarina; Spangenberg, Elin M. F.; Olsson, Johan N. G.; Stéen, Margareta (Frontiers in Veterinary Science, 2019)
Wild animals are used for research and management purposes in Sweden and throughout the world. The animals are often subjected to similar processes and risks of compromised welfare from capture, anesthesia, handling, sampling, marking and sometimes culling. However, in Sweden, the legislation differs between research and management. Whereas animal research is generally well defined and covered in the legislation, wildlife management is not. The protection of wild animals differs depending on the procedure they are subjected to, and how it is classified. In contrast to wildlife management activities, research projects have to implement the 3Rs, and must undergo ethical reviews and official animal welfare controls. It is often difficult to define the dividing line between the two categories, e.g., when marking for identification purposes. This grey zone creates uncertainty and problems beyond animal welfare, e.g., if information has been collected during management without an ethical approval, it cannot be presented in scientific journals. Thus, the legislation needs to be harmonized. To ensure similar ethical and welfare assessments for wild animals at the hands of the human, and for the benefits to science and management, we suggest that both research and management procedures are assessed by one single Animal Ethics Committee, with expertise in the 3Rs, animal welfare, wildlife population health and One Health. We emphasize the need for increased and improved official animal welfare control, facilitated by compatible legislation and a similar ethical authorization process for all wild animal procedures.